Spinal Dorsal Horn Calcium Channel α(2)δ-1 Subunit Upregulation Contributes to Peripheral Nerve Injury-Induced Tactile Allodynia - Li, Chun-Ying (Society for Neuroscience, 2004)
Peripheral nerve injury induces upregulation of the calcium channel α(2)δ-1 structural subunit in dorsal root ganglia (DRG) and dorsal spinal cord of spinal nerve-ligated rats with neuropathic pain, suggesting a role of the calcium channel α(2)δ-1 subunit in central sensitization. To investigate whether spinal dorsal horn α(2)δ-1 subunit upregulation derives from increased DRG α(2)δ-1 subunit and plays a causal role in neuropathic pain development, we examined spinal dorsal hornα(2)δ-1 subunit expression with or without dorsal rhizotomy in spinal nerve-ligated rats and its correlation with tactile allodynia, a neuropathic pain state defined as reduced thresholds to non-noxious tactile stimulation. We also examined the effects of intrathecal α(2)δ-1 antisense oligonucleotides on α(2)δ-1 subunit expression and neuropathic allodynia in the nerve-ligated rats. Our data indicated that spinal nerve injury resulted in time-dependentα(2)δ-1 subunit upregulation in the spinal dorsal horn that correlated temporally with neuropathic allodynia development and maintenance. Dorsal rhizotomy diminished basal level expression and blocked injury-induced expression of the spinal dorsal hornα(2)δ-1 subunit and reversed injury-induced tactile allodynia. In addition, intrathecal α(2)δ-1 antisense oligonucleotides blocked injury-induced dorsal horn α(2)δ-1 subunit upregulation and diminished tactile allodynia. These findings indicate that α(2)δ-1 subunit basal expression occurs presynaptically and postsynaptically in spinal dorsal horn. Nerve injury induces mainly presynaptic α(2)δ-1 subunit expression that derives from increased α(2)δ-1 subunit in injured DRG neurons. Thus, changes in presynaptic α(2)δ-1 subunit expression contribute to injury-induced spinal neuroplasticity and central sensitization that underlies neuropathic pain development and maintenance.